Lost in Babylon / 2 - Lerangis, Peter (Lerangis, Peter. Seven wonders, 2014)
Jack and his friends head to the Gardens of Babylon continuing their quest to find seven pieces of Atlantis' power that were hidden long ago and that will, if returned to Atlantis, save them from certain death due to the genetic abnormality that also gives them superior abilities.